Human rights activism and the end of the Cold War : a transnational history of the Helsinki network - Snyder, Sarah B., 1977- (New York : Cambridge University Press, 2011)
"This book explores how a network of human rights activists emerged in the aftermath of the 1975 Helsinki Final Act and over time fundamentally reshaped East-West diplomacy"--
"Two of the most pressing questions facing international historians today are how and why the Cold War ended. Human Rights Activism and the End of the Cold War explores how, in the aftermath of the signing of the Helsinki Final Act in 1975, a transnational network of activists committed to human rights in the Soviet Union and Eastern Europe made the topic a central element in East-West diplomacy. As a result, human rights eventually became an important element of Cold War diplomacy and a central component of détente. Sarah B. Snyder demonstrates how this network influenced both Western and Eastern governments to pursue policies that fostered the rise of organized dissent in Eastern Europe, freedom of movement for East Germans, and improved human rights practices in the Soviet Union - all factors in the end of the Cold War"--
Machine generated contents note: Introduction; 1. Bridging the East-West divide: the Helsinki Final Act negotiations; 2. 'A sort of lifeline': the Helsinki Commission; 3. Even in a Yakutian village: Helsinki monitoring in Moscow and beyond; 4. Follow-up at Belgrade: the United States transforms the Helsinki process; 5. Helsinki watch, the IHF, and the transnational campaign for human rights in Eastern Europe; 6. Human rights in East-West diplomacy; 7. 'A debate in the fox den about raising chickens': the Moscow conference proposal; 8. 'Perhaps without you, our revolution would not be'; Conclusion.
Includes bibliographical references and index.
Keywords: Human rights; Human rights advocacy; Cold War